AB0533 POSITIVE RATE OF SMALL INTESTINAL BACTERIAL OVERGROWTH TEST (SIBO) WAS SIGNIFICANT CORRELATIONS TO DISEASE ACTIVITY OF PRIMARY SJOGREN'S SYNDROME (PSS). (June 2019) - Li, Xiaodong; Xiao-Feng, LI; Gao, Chong; Dong, Sha; Zhang, Sheng-Xiao; Zhao-Hua, LI
Abstract : Background: Primary Sjogren's syndrome (pSS) is a chronic inflammatory autoimmune disease that primarily affects the exocrine glands, which is involved in gastrointestinal unavoidably. Once intestinal flora imbalance, it will have a major impact on health. The Small intestinal bacterial overgrowth test (SIBO) is an important method for detecting bacterial growth in the small intestine. Objectives: To investigate the difference in the positive rate of SIBO between disease active and stable patients with pSS, and to retrospectively analyze the correlation between disease activity and SIBO. Methods: Total 51 patients with pSS diagnosed and treated in our hospital were selected as subjects of this study from October 2018 to December 2018, according to the PSS Disease Activity Rating System (SSDAI) scores. They were divided into Group A: active period (point≥5 points), 25 cases and group B: stable period (point<5 points), 26 cases. Two sets of clinical data were collected, including SSDAI scores and SIBO. The difference between the percentage of active and stable SIBO positive patients was compared. The maximum sum of hydrogen and methane in the two groups was tested by rank sum test, and the correlation between pSS disease activity and SIBO positive rate was analyzed. Results: The positive rate of SIBO in patients with active pSS was significantly higher than that in stable phase, and the difference was statistically significant (P=0.026), as shown in Table 1 . The two groups were compared with H2MaX or CH4MaX, and the Mann-Whitney U test results were statistically significant (P=0.001, P=0.006), as shown in Table 2 . Conclusion: SIBO positive rate was significant correlations to pSS disease activity. So, correcting intestinal flora imbalance combined with conventional treatment may bring greater benefits to patients with Sjogren's syndrome. References: [1] LazarosI, Sakkas, Theodora, Simopoulou, Dimitrios, Daoussis, Stamatis-Nick, Liossis, Spyros, Potamianos.Intestinal Involvement in Systemic Sclerosis: A Clinical Review. [J]. Digestive diseases and sciences, 2018, 63(4):834-844. [2] Hongjun, Zhao, Lijuan, Zhao, Wei, Shi, Hui, Luo, Liping, Duan, Yunhui, You, Yisha, Li, Xiaoxia, Zuo.Is it bowel-associated dermatosis-arthritis syndrome induced by small intestinal bacteria overgrowth?[J].SpringerPlus, 2016, 5(1):1551. [3] Coyte KZ, Schluter J, Foster KR. The ecology of the microbiome:Networks, competition, and stability [J]. Science, 2015, 350(6261): 663-666. [4] Schirmer M, Smeekens SP, Vlamakis H, et al. Anticancer Immunotherapy by CTLA-4 blockade relies on the gut microbiota Commensal Bifidobacterium promotes antitumor immunity and Convenience anti-PD-L1 efficacy [J]. Cell, 2016, 167 (4):1125-1136. [5] Neuman H, Koren O. The gut microbiota: a possible factor Influencing systemic lupus erythematosus [J]. Curr Opin Rheumatol, 2017, 29 (4) : 374-377. Disclosure of Interests: None declared